2008
DOI: 10.1002/mop.23511
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the phase speed of surface-plasmon wave at the planar interface of a metal and a chiral sculptured thin film

Abstract: The solution of a boundary-value problem formulated for a modified Kretschmann configuration shows that the phase speed of a surface-plasmon wave guided by the planar interface of a sufficiently thin metal film and a chiral sculptured thin film (STF) depends on the vapor incidence angle used while fabricating the chiral STF by physical vapor depoistion. Therefore, it may be possible to engineer the phase speed quite simply by selecting an appropriate value of the vapor deposition angle (in addition to the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The resulting assembly is a sculptured thin film (STF) that is structurally chiral (Lakhtakia & Messier 2005), just like a chiral smectic liquid crystal (de Gennes & Prost 1993). In the Kretschmann configuration (Kretschmann & Raether 1968;Simon et al 1975), SPP wave propagation along the planar interface of a metal and a structurally chiral material has been theoretically demonstrated (Lakhtakia 2007); furthermore, we recently showed that the choice of the vapour incidence angle c v during fabrication must significantly affect the propagation characteristics (Lakhtakia & Polo 2008b), if the structurally chiral material is a chiral STF.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting assembly is a sculptured thin film (STF) that is structurally chiral (Lakhtakia & Messier 2005), just like a chiral smectic liquid crystal (de Gennes & Prost 1993). In the Kretschmann configuration (Kretschmann & Raether 1968;Simon et al 1975), SPP wave propagation along the planar interface of a metal and a structurally chiral material has been theoretically demonstrated (Lakhtakia 2007); furthermore, we recently showed that the choice of the vapour incidence angle c v during fabrication must significantly affect the propagation characteristics (Lakhtakia & Polo 2008b), if the structurally chiral material is a chiral STF.…”
Section: Introductionmentioning
confidence: 99%